Fragility Curves for Wide-Flange Steel Columns and Implications for Building-Specific Earthquake-Induced Loss Assessment. Issue 3 (August 2018) - Elkady, Ahmed; Ghimire, Subash; Lignos, Dimitrios G.
Building-specific loss assessment methodologies use component fragility curves to compute expected losses in the aftermath of earthquakes. Such curves are not available for steel columns assuming they remain elastic because of capacity design considerations. Nonetheless, first-story steel columns in moment-resisting frames (MRFs) are expected to experience damage through flexural yielding and formation of geometric instabilities. This paper uses an experimental database that was recently assembled to develop two sets of univariate drift-based column fragility curves that consider the influence of loading history. Ordinal logistic regression is also employed to develop multivariate fragility curves that capture geometric and loading parameters that affect column performance. The implications of the proposed fragility curves for building-specific loss assessment are demonstrated using an eight-story office building with steel MRFs. It is shown that structural repair costs in this case may increase by 10%, regardless of seismic intensity, when column damage is considered. Similarly, the contribution of structural component repairs to expected annual losses may double over the building's life span.